2019
DOI: 10.3390/nu11112777
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Osthole on Human Breast Cancer Cell Progression via Induction of Cell Cycle Arrest, Mitochondrial Dysfunction, and ER Stress

Abstract: Background: Breast cancer is the most commonly diagnosed cancer and the second leading cause of cancer death in women. Although, recently, the number of pathological studies of breast cancer have increased, it is necessary to identify a novel compound that targets multiple signaling pathways involved in breast cancer. Methods: The effects of osthole on cell viability, apoptosis, mitochondria-mediated apoptosis, production of reactive oxygen species (ROS), and endoplasmic reticulum (ER) stress proteins of BT-47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Novel Target of OST. An increasing number of studies revealed that OST acted as an inhibitory role in the oncogenesis and development of BrCa [7][8][9]; there is still a lack of systematic research on its molecular mechanisms. To obtain a comprehensive insight into its molecular mechanisms, we use the "limma" R package to extract DEGs between the control and the treatment group.…”
Section: Systematic Bioinformatics Analysis Reveals Gng7 As Amentioning
confidence: 99%
See 1 more Smart Citation
“…Novel Target of OST. An increasing number of studies revealed that OST acted as an inhibitory role in the oncogenesis and development of BrCa [7][8][9]; there is still a lack of systematic research on its molecular mechanisms. To obtain a comprehensive insight into its molecular mechanisms, we use the "limma" R package to extract DEGs between the control and the treatment group.…”
Section: Systematic Bioinformatics Analysis Reveals Gng7 As Amentioning
confidence: 99%
“…OST has been shown to significantly inhibit the growth and metastasis of BrCa, thus serving as an effective candidate drug for the comprehensive treatment of BrCa [ 7 , 8 ]. Although several studies have revealed the molecular mechanisms of OST in the treatment of BrCa [ 9 ], there is still a lack of systematic research on its molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Because the expression of CDK inhibitors in these cells may be insufficient, the G 1 phase of the cell cycle arrest provides cells with a repair mechanism or follows the pathological changes ( 27 ). Therefore, targeting the cell-cycle disorders have been considered promising targets for cancer treatment ( 28 ). Results from flow cytometry showed that cells in the G 0 /G 1 phase increased and those in the S phase decreased in Eupafolin-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that osthole-induced antitumor effects is relevant to ROS overproduction [26]. Although different forms of PCDs have different molecular mechanisms, it seems that they cannot bypass the key link of ROS generation [12].…”
Section: Discussionmentioning
confidence: 99%